PENGARUH METODE PEMBELAJARAN MATEMATIKA DENGAN CONCEPT-RICH INSTRUCTION TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMPN 3 BANDUNG TULUNGAGUNG PADA MATERI ARITMATIKA SOSIAL - Indi Ratnani; Dian Septi Nur Afifah (Jurnal Kajian Pembelajaran Matematika, 2018)
The purpose of this research is to know the influence of method of learning mathematics of Concept-Rich Instruction to result of learning mathematics. The type of research used is quantitative with experimental research design. The subject of this research is the students of class VII A SMPN 3 Bandung Tulungagung. The instrument used is a test of learning outcomes. The data analysis technique used SPSS 16.0 for Windows statistic with homogeneity test and normality test as pre-requisite test and t test as hypothesis test. The conclusion of this research is that there is a significant influence on the application of mathematics learning method with Concept-Rich Instruction against mathematics learning outcomes of students of class A SMPN 3 Bandung Tulungagung.Keywords : influence, learning methods, Concept-Rich Instruction, social arithmatic